World of health - Narins, Brigham 1962-. (Detroit Gale Group, 2000)
An alphabetical collection of articles on health and medical topics, theories, discoveries, concepts, and the people behind them.
Includes bibliographical references (p. 1277-1281) and index.
Keywords: Medicine -- Juvenile literature; Health -- Juvenile literature; Health -- Encyclopedias; Medicine -- Encyclopedias